Trypanosoma cruzi infection disturbs mitochondrial membrane potential and ROS production rate in cardiomyocytes - Gupta, Shivali (2009)
In this study, we investigated the role of Trypanosoma cruzi invasion and inflammatory processes in reactive oxygen species (ROS) production in mouse atrial cardiomyocyte line (HL-1) and primary adult rat ventricular cardiomyocytes. Cardiomyocytes were incubated with T. cruzi (Tc) trypomastigotes, Tc lysate (TcTL) or Tc secreted proteins (TcSP) for 0-72 h, and ROS measured by amplex red assay. Cardiomyocytes infected by T. cruzi (but not those incubated with TcTL or TcSP) exhibited a linear increase in ROS production during 2-48 h post-infection (max.18-fold increase) which was further enhanced by recombinant cytokines (IL-1β, TNF-α and IFN-γ). We observed no increase in NADPH oxidase, xanthine oxidase, and myeloperoxidase activities, and specific inhibitor of these enzymes did not block the increased rate of ROS production in infected cardiomyocytes. Instead, the mitochondrial membrane potential was perturbed, and resulted in inefficient electron transport chain (ETC) activity, and enhanced electron leakage and ROS formation in infected cardiomyocytes. HL-1 rho (ρ) cardiomyocytes lacked a functional ETC, and exhibited no increase in ROS formation in response to T. cruzi. Together, these results demonstrate that invasion by T. cruzi and inflammatory milieu affect mitochondrial integrity and contribute to electron transport chain inefficiency and ROS production in cardiomyocytes.